Large-aperture refractive lenses for momentum-resolved spectroscopy with hard X-rays - Fukui, Hiroshi (International Union of Crystallography, 2013)
One-dimensional kinoform and prism refractive lenses with large aperture and high transmittance at 22 keV have been investigated. A 12.0 µm focus size (full width at half-maximum) and an effective aperture of 0.85 mm, at a focal length of 705 mm and 21.747 keV, were achieved.